Pendekatan Design Thinking untuk Meningkatkan Pengalaman Pelanggan pada Usulan Sistem Bisnis Kuliner Warmindo berbasis Digital - Setyawan, Ivan Dwi; Islamy, Daviq Nazril; Syahhari, Imam; Intani, Rofiqi Ayu; Tridalestari, Ferra Arik (INTEGER: Journal of Information Technology, 2025)
In the digital era, information systems play a crucial role in enhancing operational efficiency and customer satisfaction across various sectors, including the culinary industry. This research aims to develop digital solutions for Warmindo (Warung Makan Indomie), a popular culinary business model in Indonesia. Using a Design Thinking approach, this study identifies the main issues in Warmindo services, such as long queues, order entry errors, and limited payment methods. The proposed solution is a web-based or mobile app ordering system that integrates a digital menu, an automatic queue system, and electronic payment methods. The implementation of this information system is expected to improve Warmindo's operational efficiency and provide a better customer experience. The trial results show that this solution successfully reduces wait times, improves order accuracy, and enhances customer satisfaction. This study underscores the importance of digitalization in the culinary business as a strategy to adapt to the increasingly dynamic market demands.